Analisis Pemanfaatan E-Arsip pada Bagian Administrasi Kementerian – Kementerian Keuangan - Silvia Harviana; Christian Wiradendi Wolor; Adnan Kasofi (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This research employs a qualitative method with a case study approach. Data analysis was conducted through stages of data collection, reduction, presentation, and verification. The unit of analysis in this study is the utilization of e-archive systems in the administrative department of the Ministry of Finance. The results show that the implementation of e-archive systems, such as NADINE and the archiving module in the Satu Kemenkeu super app, has improved the efficiency and effectiveness of document management. The system simplifies filing, retrieval, and document distribution processes while supporting paper usage reduction. However, challenges remain, including limited technological infrastructure, lack of technical competence among human resources (HR), and data security risks. To address these issues, it is necessary to develop HR skills through training and technical guidance, improve technological infrastructure, and maintain systems regularly. Data protection efforts have also been implemented through the use of authenticators, identity verification, antivirus software, and firewalls managed by Pusintek. Recommendations include developing a more user-friendly system and conducting further studies with a quantitative approach in different locations to enrich findings. These optimization strategies are expected to ensure the security, confidentiality, and effectiveness of electronic archive management comprehensively.